Year of the Arab uprising : impact on Southeast Asia - James M. Dorsey (2012)
The popular revolts sweeping the Middle East and North Africa are part of a global demand for political openness and transparency. Southeast Asia has so far proven adept in its response but has yet to address fundamental issues.